Exploration of policy feedback mechanism for healthcare improvement in China: a grounded theory model - Zhu, Tuo-Dong; Yang, Ming-Jin; Wu, Hao (Frontiers in Medicine, 2025)
BackgroundDespite increasing governments’ endeavors to improve the quality of medical services focused on patient experience, it has been difficult due to a lack of systematic and replicable theories to guide healthcare improvement. This study aimed to construct a theoretical model of a policy feedback mechanism for guiding healthcare improvement based on healthcare improvement in China’s context.MethodsWe constructed a theoretical model of policy feedback mechanism for improving healthcare using a grounded theory approach to collect and analyze textual data on healthcare improvement in China.ResultsIn this study, the theoretical model of policy feedback mechanism for healthcare improvement contained five core modules: multi-level objects, policy context, policy tools driven, policy feedback process, and policy feedback results. At the theoretical level, we innovatively constructed the module of “patient feelings,” including “patient sense of gain,” “patient happiness,” and “patient sense of safety.” Practically, we generated a list of ways through the “medical organization behavior” module to enhance patient feelings.ConclusionThis model elaborated a policy feedback mechanism for healthcare improvement. This research provided theoretical and practical support for health authorities to formulate and apply various policies or initiatives to improve healthcare. Theoretically, the model innovated the development of patient feelings in the policy feedback for healthcare improvement. On the practical level, we generated specific strategies for hospitals to enhance healthcare and patient experience.